Imidacloprid poisoning in a young female: a case report - Om Prakash Bhatta; Sabita Chand; Hemant Chand; Ram Chandra Poudel; Ram Prasad Lamichhane; Abhi Kumar Singh; Nuwadatta Subedi (Journal of Medical Case Reports, 2023)
Abstract Background Imidacloprid, a neonicotinoid insecticide, is widely used in agricultural settings. Consequently, cases of accidental and suicidal poisoning are increasingly seen in clinical practice. Although cases with varied clinical presentations and toxicological profiles have been reported, standard management principles are lacking. Case presentation We present a case of Imidacloprid poisoning in a 25-year-old previously healthy indigenous Tamang female without a classic toxidrome requiring ventilatory support, complicated by a prolonged neuropsychiatric sequela. Conclusions Although uncommonly reported, imidacloprid toxicity may lead to life-threatening complications and hence should be suspected in cases of unidentified poisoning with a relevant toxidrome. Vigilance on the part of treating physicians plays a crucial role in appropriate management.